Software architecture : 14th European Conference, ECSA 2020 Tracks and Workshops, L'Aquila, Italy, September 14-18, 2020, proceedings /: 14th European Conference, ECSA 2020 Tracks and Workshops, L'Aquila, Italy, September 14-18, 2020, proceedings. (2020) - Unknown
No abstract available